2013
DOI: 10.1073/pnas.1312159110
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent imaging of drug efflux at the blood–brain barrier mediated by the transporter ABCG2

Abstract: ATP-binding cassette (ABC) transporters are a group of transmembrane proteins that maintain chemical homeostasis through efflux of compounds out of organelles and cells. Among other functions, ABC transporters play a key role in protecting the brain parenchyma by efflux of xenobiotics from capillary endothelial cells at the blood-brain barrier (BBB). They also prevent the entry of therapeutic drugs at the BBB, thereby limiting their efficacy. One of the key transporters playing this role is ABCG2. Although oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…The brain penetration of 14 C-D-luciferin in mice has been previously shown to be very low (Berger et al, 2008), which is consistent with the finding that luciferin is a Bcrp substrate (Zhang et al, 2007). Indeed, treatment with Bcrp inhibitors enhanced D-luciferin brain penetration of a low dose of D-luciferin (18 mg/kg) (Bakhsheshian et al, 2013), suggesting BBB Bcrp can limit brain availability of D-luciferin. At the D-luciferin concentrations used in most studies (and this one) (i.p.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The brain penetration of 14 C-D-luciferin in mice has been previously shown to be very low (Berger et al, 2008), which is consistent with the finding that luciferin is a Bcrp substrate (Zhang et al, 2007). Indeed, treatment with Bcrp inhibitors enhanced D-luciferin brain penetration of a low dose of D-luciferin (18 mg/kg) (Bakhsheshian et al, 2013), suggesting BBB Bcrp can limit brain availability of D-luciferin. At the D-luciferin concentrations used in most studies (and this one) (i.p.…”
Section: Discussionsupporting
confidence: 87%
“…3). Since D-luciferin is a substrate of Bcrp (Zhang et al, 2007), a transporter that can limit brain availability of D-luciferin at the BBB (Bakhsheshian et al, 2013), we treated mice with an oral dose of elacridar (100 mg/kg) for 4 hours in order to maximize the brain-to-plasma concentration (Sane et al, 2012). Elacridar increased the total MDR1-luc bioluminescent signal up to 2-fold in vehicle-and drug-treated mice (Fig.…”
Section: Mdr1-lucmentioning
confidence: 99%
“…In transgenic mice expressing the luciferase gene, activity was measured using the ABCG2 substrate D-luciferin before and after Ko143 administration (Bakhsheshian et al, 2013b). Because bioluminescence is not an option in the CNS of humans, a specific ABCG2 substrate that can be efficiently radiolabeled is needed instead.…”
Section: Ko143 Not Specific For Abcg2mentioning
confidence: 99%
“…1A) has been used over the past decade to examine the interaction between ABCG2 and pharmaceutical drugs in vitro and in vivo (Allen et al, 2002). For example, Ko143 was found to elevate mouse brain levels of the ABCG2 substrate D-luciferin in a bioluminescence-based imaging strategy (Bakhsheshian et al, 2013b). Given the frequent use of Ko143, characterization of Ko143 in terms of specificity in both human and mouse cell lines is of particular significance given the known species differences of ABC transporters.…”
Section: Introductionmentioning
confidence: 99%
“…The same group also demonstrated that D-luciferin cellular accumulation is facilitated by an uptake mechanism, likely OCTN1 (107). The work of Bakhsheshian et al (108) showed that D-luciferin entry into the brain is restricted by BCRP and that this process correlates with BCRP expression and function. This study provided the groundwork for a novel method to examine transporter function at the blood-brain barrier.…”
Section: Blimentioning
confidence: 96%